The tragedy of the commons in artisanal gold mining: evaluation of mechanisms of cooperation with simulation and economic experiments (2013)
Abstract: This thesis is about how collective action –associative entrepreneurship– can be fostered in artisanal and small-scale gold mining. This kind of association is aimed at, among other things, allowing small-scale gold miners to gather the financial capital that is required to obtain the type of technologies that reduce mercury use in the gold recovery process, and therefore the harmful effects of mercury pollution of ecosystems and human health. Given the public-good dilemma that is faced by these individuals, I study possible institutional arrangements by which associative entrepreneurship may be encouraged. The methods to achieve this include the construction of a behavioral simulation model using System Dynamics. As part of both the model building and its validation process I make use of the results of economic experiments carried out both in the lab and the field. The results of the economic experiments do not reject the hypothesis which states that sustained collective action does not self-emerge as a solution to the public-good dilemma. In this thesis I analyze two institutional arrangements: co-management and exclusion from private benefits. Of these two, only co-management shows a statistically significant impact on the establishment of a permanent collective action. However, in the field experiment this effect of co-management is undermined when it is combined with exclusion from the private benefits. From the behavioral simulation model, it is shown that reciprocity, free-riding and profit maximization are the behavioral aspects that mainly drive decision-making when dealing with the public-good dilemma. With an external intervention such as co-management, individuals get more aware of the social dilemma they face and collective action is sustained over time. From a policy viewpoint these results suggest the importance of interventions programs such as education projects, training in alternative practices and technologies, and campaigns to foster social capital. Moreover, the experimental results cast doubt on the effectiveness of economic incentives to change some practices in the production process of gold. However, simulation results show that the implementation of stricter incentives could make miners to increase their commitment to sustain the entrepreneurial organization